2017
DOI: 10.1638/2017-0010.1
|View full text |Cite
|
Sign up to set email alerts
|

SERUM FERRITIN CONCENTRATION IS NOT A RELIABLE BIOMARKER OF IRON OVERLOAD DISORDER PROGRESSION OR HEMOCHROMATOSIS IN THE SUMATRAN RHINOCEROS (DICERORHINUS SUMATRENSIS)

Abstract: The aim of this study was to determine if ferritin is a reliable biomarker of iron overload disorder (IOD) progression and hemochromatosis in the Sumatran rhinoceros (Dicerorhinus sumatrensis) by developing a species-specific ferritin assay and testing historically banked samples collected from rhinos that did and did not die of hemochromatosis. Ferritin extracted from Sumatran rhino liver tissue was used to generate antibodies for the Enzyme Immunoassay. Historically banked Sumatran rhino serum samples (n = 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 41 publications
0
11
1
Order By: Relevance
“…Although both black rhinoceroses and Sumatran rhinoceroses are susceptible to IOD, Sumatran rhinoceroses have presented with classic hemochromatosis in the absence of other disease states, whereas black rhinoceroses typically die of another primary cause and hemosiderosis is noted post-mortem (Dennis et al, 2007; Olias et al, 2012; Paglia and Tsu, 2012). Furthermore, serum ferritin concentrations in healthy black rhinoceroses can be significantly higher than those measured in Sumatran rhinoceroses that die of hemochromatosis (Roth et al, 2017; Wojtusik and Roth, 2018), Not only do these observations and data reveal the inadequacy of serum ferritin as a biomarker for IOD progression in the rhinoceros, they also suggest that the iron overload condition of these two species may differ in origin, etiology and/or impact.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Although both black rhinoceroses and Sumatran rhinoceroses are susceptible to IOD, Sumatran rhinoceroses have presented with classic hemochromatosis in the absence of other disease states, whereas black rhinoceroses typically die of another primary cause and hemosiderosis is noted post-mortem (Dennis et al, 2007; Olias et al, 2012; Paglia and Tsu, 2012). Furthermore, serum ferritin concentrations in healthy black rhinoceroses can be significantly higher than those measured in Sumatran rhinoceroses that die of hemochromatosis (Roth et al, 2017; Wojtusik and Roth, 2018), Not only do these observations and data reveal the inadequacy of serum ferritin as a biomarker for IOD progression in the rhinoceros, they also suggest that the iron overload condition of these two species may differ in origin, etiology and/or impact.…”
Section: Discussionmentioning
confidence: 85%
“…In the rhinoceros, the term iron overload disorder (IOD) was adopted in 2012 to describe the condition of excess body iron identified post-mortem in the form of excessive organ tissue hemosiderosis in this taxon, and to catalyze efforts to better understand the frequency of progression to disease-states and its role in predisposing individuals to unrelated diseases (Dennis et al, 2012). IOD affects two of the four rhinoceros species maintained in zoos, the black rhinoceros ( Diceros bicornis ) (Olias et al, 2012; Paglia and Tsu, 2012) and the Sumatran rhinoceros ( Dicerorhinus sumatrensis ) (Paglia and Tsu, 2012; Roth et al, 2017). Both species are browsers in the wild with diets consisting primarily of shrubs, bushes, leaves, twigs, tree branches, and bark (Hall-Martin et al, 1982; Van Strien, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…In humans, let-7g may be regulated by the heavy chain subunit of ferritin, an iron storage protein responsible for iron uptake and release ( 29 ). Ferritin is often used as an indicator of iron overload in humans; however, there is debate over the usefulness of ferritin as an IOD biomarker in rhino species ( 10 , 11 ). In this study, correlation analysis between let-7g and ferritin concentrations in black rhinos ( 11 ) and Sumatran rhinos ( 10 ) did not reveal strong correlations (r = −0.29 and r = 0.18, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…Even if liver biopsy remains the gold standard for definitive diagnosis of iron overload syndromes [35] and has already been performed in a live captive BR confirming diffuse hemosiderosis [36], this procedure is technically challenging due to the animal’s size, the depth of the liver, the difficulty of ultrasound and the skin thickness. Despite having been used in several studies [8,37], ferritin is not specific for iron overload syndromes [38] and is reported as a poor biomarker for IOD progression in Sumatran rhinoceroses, another species of browser rhinoceros [39]. As a consequence, serum iron, TIBC (Total Iron Binding Capacity) measurement and subsequent calculation of Transferrin Saturation may be currently the best tools for guiding ante-mortem diagnosis and prognosis of IOD in captive BR as suggested by several studies [10,33,34,36] and should be included in regular blood tests when checking for the health status of captive BR.…”
Section: Discussionmentioning
confidence: 99%